FAKTOR FAKTOR YANG MEMPENGARUHI PENGGUNAAN ALAT KONTRASEPSI PADA SUAMI - Endang Murniasih (JKM (Jurnal Kebidanan Malahayati), 2021)
Background the Family Planning Program (KB) has been established since 1970, together with the establishment of the National Family Planning Coordinating Board (BKKBN). The number of active family planning participants of husbands in Lampung Province tended to be low, namely 0.74% in MOP and 1.95% in condom users. The number of contraceptive users of husbands at Pinang Jaya Health Center is only 0.3%. The purpose of this study is to know the influence  factor factor to users of contraception on husbands at Pinang Jaya Health Center Bandar Lampung City in 2018.Method of research used in this study is analytic observational and cross sectional design. Population is fertile age couples (PUS) in Pinang Jaya health centers as much as 987. Samples are counted as much as 312. Data collection techniques use primary data and data analysis using chi square and multiple logistic regression processed with computer programs. Results showed the use of contraception of husbands at Pinang Jaya Public Health Center in Bandar Lampung City 44.2%, good knowledge 50.6%, positive attitude 45.5%, higher education 60.3%, The results of hypothesis testing indicate there is influence of knowledge (p=0,000; OR=7.77), attitude (p=0,000; OR=8,01), education (p=0,000; OR=5,96) with the use of contraceptives of husbands. from these factors it is known that knowledge is the most dominant factor (p=0,000 and OR=4,380). Conclusion The most dominant factor influencing the use of contraceptives by husbands at the Pinang Jaya Health Center Bandar Lampung City is the knowledge variable (p = 0.000 and OR = 4.380) Suggestions for puskesmas are expected to create a limited club or class for fathers or husbands to facilitate the implementation of counseling about family planning and facilitate the counseling process for husbands about male contraceptives Keywords: factor factor,Contraceptives of husbands. ABSTRAK Latar Belakang Program Keluarga Berencana (KB) sudah ditetapkan sejak tahun 1970, bersamaan dengan dibentuknya Badan Koordinasi Keluarga Berencana Nasional (BkkbN). Jumlah peserta KB aktif pada suami di Provinsi Lampung cenderung rendah yaitu 0,74% pada MOP dan 1,95% pengguna kondom. Angka pengguna kontrasepsi pada suami di Puskesmas Pinang Jaya hanya 0,3%.Tujuan penelitian ini adalah diketahui factor factor yang mempengaruhi pengguna alat kontrasepsi pada suami di Puskesmas Pinang Jaya Kota Bandar Lampung tahun 2018.Metode yang digunakan dalam penelitian ini adalah observasional analitik dan desain cross sectional. Populasi adalah Pasangan Usia Subur (PUS) di Puskesmas Pinang Jaya sebanyak 987. Sampel dihitung sebanyak 312. Tehnik pengumpulan data menggunakan kuesioner dan analisis data menggunakan chi square dan regresi logistik berganda yang diolah dengan program komputer.Hasil penelitian Univariat menunjukkan penggunaan alat kontrasepsi pada suami di Puskesmas Pinang Jaya Kota Bandar Lampung 44,2%, pengetahuan baik 50,6%, sikap positif 45,5%, pendidikan tinggi 60,3%, Hasil uji bivariat menunjukkan ada pengaruh pengetahuan (p=0,000;OR=7,77), sikap (p=0,000;OR=8,01), pendidikan (p=0,000;OR=5,96), dengan penggunaan alat kontrasepsi pada suami.Kesimpulan Faktor paling dominan berpengaruh dengan penggunaan alat kontrasepsi pada suami di Puskesmas Pinang Jaya Kota Bandar Lampung adalah variabel pengetahuan (p=0,000 dan OR=4,380)Saran Bagi puskesmas di harapkan Membuat klub terbatas atau kelas ayah atau suami untuk memudahkan pelaksanaan penyuluhan tentang KB dan memduahkan proses konseling suami tentang alat kontrasepsi pria KB Pria Kata Kunci: faktor factor, Alat kontrasepsi suami;